COMPETITION OF CRIMINAL LAW NORMS UNDER THE NEW RA CRIMINAL CODE - Gevorgyan, Tatevik (State and Law, 2022)
The commission of several crimes by one person requires a special approach by the government. The need to counteract such criminal manifestations determines the scientific and practical development of the competition of criminal law norms. The competition of criminal law norms can take place at the stage of various criminal law relations, and only their legal assessment can have an accurate qualification and disclosure of a criminal act or acts. An innovation in this respect is the consolidation of this institution and the definition of this concept in the new Criminal Code of the Republic of Armenia. The author first refers to the substantive diversity of the competition of norms, and then offers their appropriate qualification. The author greatly appreciates the legislative provisions on the competition of criminal law norms, stipulated in the separate part of the new Criminal Code of the Republic of Armenia, noting that these provisions can contribute to solving problems that arise in practice.